212 Routine hysterectomy should not be performed after radiotherapy end in women with endocervical adenocarcinoma. (18th September 2019) - Souza, ECA; Santos, DZ; Silva, NG; Sallum, LF; Vale, DB; Braganca, JF; Teixeira, J
Abstract : Objectives: To evaluate the prognosis of hysterectomy post-radiotherapy in women with endocervical adenocarcinoma from a university hospital (Unicamp/Brazil), compared to those undergoing exclusive radiotherapy. Methods: Were selected 80 cases of women with endocervical adenocarcinomas FIGO IB to IIIB from 1988–2015, 39 treated with radiotherapy followed by hysterectomy and isolated radiotherapy for 41. Disease-free interval (DFI) and overall survival (OS) were analysed using Kaplan-Meier curves and log-rank test. Results: There was no difference in OS between the groups (P=0.579) or in the DFI (p=0.963). It was observed that the DFI in patients with residual disease was lower, however without statistical significance (P=0.072). Recurrences were observed in 9/39 patients of the hysterectomy group and 10/41 patients of the isolated radiotherapy group. Residual disease in the hysterectomy group was associated with a higher rate of local and distance recurrence (P=0.028). Conclusions: There were no differences in recurrence rates, disease-free interval, and overall survival among the groups, although the detection of residual disease in the hysterectomy was associated with a higher occurrence of recurrences. The findings do not support the routine hysterectomy in women previously irradiated in endocervical adenocarcinoma.